The Contribution of Cultural Art in the Creation of Liong Ornament on the Roof of Tay Kak Sie Temple Semarang Central Java - Mustaqin, Khairul (PANGGUNG, 2017)
AbstractThe Liong Ornaments on the roof of Tay Kak Sie Temple in Semarang Central Java are influenced by the various contributions of art and culture to its creation. The issues raised in this research, namely: 1) How Liong ornaments form on the roof of Tay Kak Sie Temple are; 2) How art elements on Liong ornaments on the roof of Tay Kak Sie Temple; 3) What are the contributions of art and culture to the creation of Liong ornaments on the roof of Tay Kak Sie Temple Semarang Central Java. The purpose of this study is to provide an explanation of Liong ornament form on the roof of Tay Kak Sie Temple; art elements on Liong ornaments on the roof of Tay Kak Sie Temple; and cultural art contribution to the creation of Liong statue ornament on the roof of Tay Kak Sie Temple Semarang Central Java. This research uses qualitative method with case study approach. Ornaments Liong statue on the roof of Tay Kak Sie Temple is a three-dimensional work with simplification and deformation techniques. Liong statue ornament is an imitative form of Chinese mythology animal. The texture of the ornament, ie smooth, smooth wavy, and rough. Liong Ornaments use seven colors and contain elements of blue monochromatic color. Liong Ornaments are included in imitative artwork with a style of naturalist expression. Expression of ornaments, namely anger, ambition, and firmness. Liong ornaments form on the roof of Tay Kak Sie Temple Semarang Central Java influenced by the factors of artists, culture, the influence of the Ming Dynasty, the location of the temple, and trust.Keywords: Contribution of Cultural Art, Creation, Liong Ornament, Temple